Pengaruh edukasi stimulasi terhadap perkembangan kognitif anak usia dini - Marilin Kristina; Ruly Nadian Sari (Journal Of Dehasen Educational Review, 2021)
In pre-school age, children generally show significant development, especially in aspects of cognitive development.This happens because in pre-school age is a golden age that is often called golden age.Cognitive development is not necessarily able to take place optimally without the stimulus or stimulation given to pre-school age children.Lack of stimulation given to pre-school age children can result in loss of brain cells function so that it will impact the slow cognitive development and impact on the child's ability to process the information received.The research method in this study is to use literature studies based on the results of analysis of the results of research used as literature in this study.The procedure in conducting literature studies in this study is to determine the formulation of problems, find relevant literature, evaluate the data obtained, analyze and then interpret the data that has been obtained.Based on the study of literature can be obtained the conclusion that the provision of stimulation education in pre-school age children can improve the cognitive development of pre-school age children